Pengaruh Display Produk dan Store Atmosfer Terhadap Impulse Buying Melalui Emotional Response Sebagai Variabel Intervening Pada Customer Matahari Medan Fair - Sijabat, Yeni Anggriani; Amelia, Wan Rizca (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This article or writing aims to determine the influence of product displays and store atmosphere on impulse buying through emotional response as an intervening variable for Matahari Medan Fair customers. Apart from that, to find out whether the product display is able to attract consumers' attention to the goods being sold, be it communication information, promotions or visuals that attract consumers. Data was collected through a questionnaire. The population size could not be determined, so we produced a sample using hair's opinion, bringing the total to 96 respondents. Data analysis was carried out via PLS-SEM using the SmartPLS 3.0 program. The research results show the conclusion that product display has a positive and significant effect on impulse buying, as proven by p-values 0.000 0.05. Store Atmosphere has a positive and significant effect on impulse buying, as proven by p-values 0.005 0.05. then indirectly, Product Display through Emotional Response to Impulse Buying has a positive and significant effect on impulse buying, as proven by p-values 0.012 0.05. Store Atmosphere through Emotional Response to Impulse Buying has a positive and significant effect on impulse buying as proven by p-values 0.003 0.05